Pengaruh JUB, BI-Rate Dan Covid-19 Terhadap Permintaan Kredit Bank di Indonesia - Ghea Safa Ramadhani; Muhammad Hartana Iswandi Putra (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to analyze the influence of the money supply (M2), the BI Rate, and the COVID-19 pandemic on the demand for bank credit in Indonesia. Credit demand is an important indicator in describing economic activity and financial system stability. This study uses monthly secondary data from January 2017 to December 2023. The analysis method used is Ordinary Least Squares (OLS), which allows for quantitative estimation of the linear relationship between the independent and dependent variables. The results show that the money supply (M2) has a positive and significant effect on credit demand. This suggests that increased liquidity in the economy encourages increased lending activity by the household and corporate sectors. Conversely, the BI Rate shows a negative and significant effect on credit demand, indicating that an increase in the benchmark interest rate has reduced public interest in accessing financing through banks. This finding is in line with conventional monetary theory, which states that interest rates play a crucial role in controlling aggregate demand, including credit demand. The dummy variable for the COVID-19 pandemic shows a negative but insignificant effect on credit demand. This implies that although the pandemic has had a broad social and economic impact, its impact on credit demand is relatively small when monetary variables such as M2 and the BI Rate are taken into account. Overall, the research findings confirm that monetary policy instruments, particularly controlling the money supply and interest rates, play a significant role in influencing the dynamics of credit demand in Indonesia. Meanwhile, external shocks such as the pandemic tend to be more effectively responded to through medium- and long-term fiscal and structural policies.